2021
DOI: 10.15561/20755279.2021.0406
|View full text |Cite
|
Sign up to set email alerts
|

The coordination abilities development in female students based on dance exercises

Abstract: Background and Study Aim. The physical fitness of students is characterized by the level of their abilities development to perform movements of varying complexity. One of the important components in the system of movements is coordination skills. The aim of the study is to identify the level of special and general coordination of students majoring in "Choreography" and provide recommendations for the development of coordination skills in the process of studying modern-jazz dance. Material and Methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However the highest values of coordination skills can be reached between 17 and 20 years of age. Following this idea, a number of studies have obtained good results in developing coordination abilities in samples of university students [19,20]. It demonstrates that development of coordination abilities is an overgoing process.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However the highest values of coordination skills can be reached between 17 and 20 years of age. Following this idea, a number of studies have obtained good results in developing coordination abilities in samples of university students [19,20]. It demonstrates that development of coordination abilities is an overgoing process.…”
Section: Discussionmentioning
confidence: 94%
“…Our study findings are consistent with recent pedagogical experiments on female university students attaining physical education classes. In two cases the intervention consisted in choreography [23] and dance [19] exercises and there were effective in developing the coordination skills. Another study on the same age range and gender [20] demonstrated that the coordination skills are more likely to be improved compared to speed as a skill related fitness component.…”
Section: Discussionmentioning
confidence: 99%
“…To master good coordination skills, it is necessary to repeat exercises directed towards movement automation, so that coordination skills are not innate but must be learned and repeated continuously (Limanskaya et al, 2021). If children have low or poor motor coordination skills, the problem not only hinders the development of children's motor skills but can also affect academic achievement, perceived competence, activeness in participating in physical activities and social interactions, and comfort.…”
Section: Discussionmentioning
confidence: 99%
“…M is the muscle strength matrix of body movement. 6 The vector G represents the damping weighted least squares vector of the chain articulation torque:…”
Section: Investigation Methodsmentioning
confidence: 99%